THE ROLE AND IMPORTANCE OF STRATEGIC PLANNING IN MARKETING - Xo'jayorova Saodat Obid qizi; Zubaydova Nilufar Negmatullayevna (TADQIQOTLAR.UZ, 2024)
Abstract. Marketing strategy is the marketing of a firm’s target market is a master program that represents the activities of the company and includes the process of achieving its goals through the development and implementation of a long-term marketing mix (marketing mix). Separate product, pricing, distribution, sales and communication policies are defined for each segment of the market. The marketing strategy determines which product (service) the firm should enter, which market, and when. The following marketing strategies have been tested and successfully used by companies in the world market practice.